Gender Interaction: Exploring How Shopee Mobile Technology Shapes Consumer Decisions Through the Lens of Consumer Enjoyment - Talita, Febrina; Wahyuningsih, Wahyuningsih; Santi, Ira Nuriya (Universitas Brawijaya, Indonesia, 2024)
The evolution of e-commerce from simple websites that facilitate sales transactions to integrated mobile apps has been fuelled by a significant surge in user demand. This transformation, marked by the dominance of mobile devices in accessing e-commerce platforms such as Shopee, underscores the importance of understanding consumer behavior and preferences in the context of mobile shopping. The findings of this study provide valuable insights into how perceived usefulness (PU) and perceived ease of use (PEOU), as well as gender, influence purchasing decisions on Shopee Mobile. We conducted an online survey using Google Forms to collect the research data. A total of 210 respondents were successfully obtained and processed the data. The survey respondents are Shopee Mobile application users who live in Palu City. The PLS SEM 3 data analysis method employs the JASP tool for data processing. The study's results show that perceived usefulness and perceived ease of use do not significantly influence purchase decisions. However, when mediated by consumer enjoyment, perceived usefulness and perceived ease of use significantly influence purchase decisions; the moderating effect of gender is not significant. The findings of this study are very useful for managers or company leaders in developing technological application innovations to increase the number of application users and can influence consumer choices in making purchasing decisions.